Distinction (on affinity) by Guy d’Evreux - Elizaveta Romanovskaya (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология, 2025)
This publication offers a translation of a distinction (from latin — distinctiones) from Summa Guiotina, the collection of sermons extremely popular in the late Middle Ages. The translation is accompanied by an article presenting the genre of distinctiones. There is also a background to Summa Guiotina and its author, Guy d'Evreux, who lived during the second half of the thirteenth century. The translation presented is based on the transcription of a Parisian manuscript BnF, Ms. lat. 15966 originating from the Sorbonne College.